Teoria dos princípios trabalhistas: a inserção do direito do trabalho no modelo metodológico pós-positivista - Molina, André Araújo (2010)
Law as a social phenomenon may be object of study in various knowledge fields, depending on the observer s view. Jurists have always tried to answer What are rights? (object of Juridical Science), as well as what the best methods for this study are. Two big groups were formed. On one side the jusnaturalists; on the other side those who deny the existence of rights besides the positive right, making the object of law science coincide with the law imposed at certain time and space. This second group is called the positivists. Recently, a third way has been built embedded in the idea that rights are not only based on rules, as positivists want, but on rules and principles. This is an intermediary methodological position which does not deny some of the positivist theses, but aims to resume moral in Law through principles. In Brazil, this position is called postpositivist. In our point of view, only the post-positivist method is appropriate to give concreteness to the constituent ideas, creating a mechanism for enforcement of fundamental rights, because they have a framework of principles. And the Labor Law, which is inserted in the frame of the Constitution, also seeks for a new method of interpretation and application that is the post-positivist, as it is lavish in ensuring fundamental rights and the conflict between social and liberal ideals. The objective of this work is to insert the Brazilian Labor Law in the postpositivist methodology model, mainly using the principle of proportionality to consider principles in cases of collision. Therefore we analyzed the formation of labor law, showing its social-marxist origin as well as that the positivist method employed by the near unanimity of the users of labor law no longer meets the complexities of postmodernity and the guidelines of the Constitution